1975
DOI: 10.1093/nar/2.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Primary sequence of the 16S ribosomal RNA of Escherichia coli

Abstract: Recent progress in the nucleotide sequence analysis of the 16S ribosomal RNA from E. coli is described. The sequence which has been partially or completely determined so far encompasses 1520 nucleotides, i.e. about 95% of the molecule. Possible features of the secondary structure are suggested on the basis of the nucleotide sequence and data on sequence heterogeneities, repetitions and the location of modified nucleotides are presented. In the accompanying paper, the use of the nucleotide sequence data in stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
2

Year Published

1976
1976
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 42 publications
4
77
2
Order By: Relevance
“…To identify optimal SD sequences for our expression vectors, we used the Bacteroidales genome sequences available in public databases. Figure 1A shows alignment of the 3= ends of the 16S rRNA gene sequences extracted from the genome sequences of Bacteroides thetaiotaomicron VPI 5482 (29), Bacteroides vulgatus ATCC 8482 (30), Bacteroides ovatus V975 (U. Wegmann, unpublished data), Bacteroides fragilis NCTC 9343 (30), Prevotella denticola F0289 (CP002589), and Prevotella bryantii B14 (31) with the sequenced 3= ends of 16S rRNA sequences from Escherichia coli (32,33), Bacillus subtilis (34), Bacillus stearothermophilus (35) (now Geobacillus stearothermophilus), and Lactococcus lactis (36), which demonstrates the perfect sequence conservation with regard to the 3= ends of the 16S rRNAs. In the cases of B. thetaiotaomicron, B. vulgatus, P. denticola, and P. bryantii, the 16S rRNA genes annotated in the respective genomes were extended with additional downstream sequence data on the basis that all rRNA gene operons present in the genome were followed by the same stretch of sequence that would be transcribed into the same 3= ends as those reported for Gram-positive 16S rRNA sequences.…”
Section: Resultsmentioning
confidence: 99%
“…To identify optimal SD sequences for our expression vectors, we used the Bacteroidales genome sequences available in public databases. Figure 1A shows alignment of the 3= ends of the 16S rRNA gene sequences extracted from the genome sequences of Bacteroides thetaiotaomicron VPI 5482 (29), Bacteroides vulgatus ATCC 8482 (30), Bacteroides ovatus V975 (U. Wegmann, unpublished data), Bacteroides fragilis NCTC 9343 (30), Prevotella denticola F0289 (CP002589), and Prevotella bryantii B14 (31) with the sequenced 3= ends of 16S rRNA sequences from Escherichia coli (32,33), Bacillus subtilis (34), Bacillus stearothermophilus (35) (now Geobacillus stearothermophilus), and Lactococcus lactis (36), which demonstrates the perfect sequence conservation with regard to the 3= ends of the 16S rRNAs. In the cases of B. thetaiotaomicron, B. vulgatus, P. denticola, and P. bryantii, the 16S rRNA genes annotated in the respective genomes were extended with additional downstream sequence data on the basis that all rRNA gene operons present in the genome were followed by the same stretch of sequence that would be transcribed into the same 3= ends as those reported for Gram-positive 16S rRNA sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Part of the PCR results are shown in Figs 1 and 2. Kiss et al (1977) reported that there are several rRNA operons (rRNA A : G) for E. coli cells while Ehresmann et al (1975) reported the heterogeneity in 16S rRNA sequences for E. coli. Thus, data in Table 3 may imply that for all E. coli strains, the 16E1 target sequence is present in the V 3 region.…”
Section: Detection Specificity For Primer Sets Of 16e1/16e2 16e1/16ementioning
confidence: 99%
“…The generally rather weak cross-linking by formaldehyde of the RNA binding proteins in the 30-S subunit has already been commented upon in the previous section, and several other proteins are either very weakly linked or not observable (see Table 16 16-S R N A . The 16-S RNA is divided into sections as in [36]. Nucleotide sequences contained in ribonucleoprotein fragment 11 are described in the following paper [21] and those from fragment 111 in [5] 2).…”
Section: Analysis Of 30-s Subunit Rna Regionsmentioning
confidence: 99%